World Conspiracy on Power and Politics - Mohd Hisyamuddin, Basabah (2016)
World conspiracy through the power and politics against Islam particularly bring instability on the world's structure and international security. The crisis and conflicts involving Islamic countries is due to a planned conspiracy by the conspirators made of the group or secret organizations. This paper in particular be discussing on how this conspiracy is being carried out through politics to achieve the maximum power in achieving the agenda of the conspirators to dominate the Islamic world. In addition, this paper will examine the factors that contribute to a occurrence of a world wide conspiracy to dominate the Islamic world through power and politics. Based on the title of this paper, there are several independent variables that will be analyzed based on the final goal of the conspiracy. While the dependent variable regarding the power and politics will focus on why the power and politics on the agenda of the conspirators in the success of their desires to dominate the Islamic world. This study will significantly contribute to an accurate understanding of how the conspiracy was carried out through politics to achieve the power to conquer the world in absolute terms and it must start with conquering the Islamic world first.